The Use of The Timeline Mapping Method Based on Blooket in an Effort to Improve Students’ Conceptual Understanding in Islamic Cultural History Subjects - Diandra Salsa Maulana; Herdianto Wahyu Pratomo; Abu Syhabudin (FKIP - Universitas Riau, 2026)
This research is motivated by the low conceptual understanding of students in the subject of Islamic Cultural History at Madrasah Aliyah, caused by conventional teacher-centered learning methods and the suboptimal use of digital media in the learning process. This study aims to improve students’ conceptual understanding through the application of the Timeline Mapping method integrated with a digital game-based learning media, namely Blooket. The research method used in Classroom Action Research with the Kemmis and McTaggart model, conducted in two cycles. The research subject were 19 students of class XI-A at Ma Al Fajar Kalapadua, Lemahsugih District, Majalengka Regency, West Java Province, academic year 2025/2026. Data were collected quantitatively through pretets and posttest, and qualitatively through observation. The result showed a significant improvement in all indicators of students’ concepual understanding. Classical completeness increased from 21.05% in the pre-cycle to 31.57% in cycle I, and reached 89.47% in cycle II. The class average score also increased from 60.00 in the pre-cycle to 66.05 in cycle I and 83,42 in cycle II. Thus, the combination of the Timeline Mapping method with Blooket media has proven effective in improving students’ conceptual understanding in the subject of Islamic Cultural History at Madrasah Aliyah.